Graphene/Ni Wire Foam with Multivalent Manganese Oxide Catalysts for Li-O2 Battery Cathode. (23rd June 2017) - Liu, Chueh; Li, Changling; Mutlu, Zafer; Ozkan, Cengiz S.; Ozkan, Mihrimah
ABSTRACT: Herein, commercial Ni foam coated with self-assembled and linearly-aligned Ni wires is utilized as a cost-effective current collector for application in Li-O2 battery. The Ni wires are furthered deposited with graphene layers (g-Ni wire) to improve electrical conductivity. Multivalent Mn oxides consisting of Mn3 O4, Mn2 O3 and MnCO3 are used as effective oxygen reduction (ORR) and evolution reaction (OER) catalysts deposited on g-Ni wire current collectors. Specific capacities are respective ∼100 and ∼170 mAh g -1 without or with O2 introduction into the cell. The relative facile synthesis process requiring merely solution-based synthesis at ambient pressure, low temperature and short process time renders the Mn oxides/g-Ni wire electrode promising for Li-O2 battery application.